KARAKTERISTIK DAN KESEDIAAN CAREGIVERS KELUARGA DARI PASIEN DENGAN PENYAKIT KRONIS TENTANG PEMBENTUKAN SUPPORT GROUP - Sri Rahayu, Teti Rahmawati (Institut Kesehatan Hermina, 2019)
Family caregivers have a crucial role in patients with chronic diseases. During caregiving care, they might have various experiences, successes, failures, problems, and also obstacles in caring the patients. Surely, they might feel stressed, anxious, frustrated, depressed, feel alone, and health problems. Subsequently, they need public attention to by finding solutions such as the idea of creating a group. The purpose of this study was to identify the characteristics and willingness of family caregivers of patients with chronic diseases related to creating support groups. Quantitative research with cross-sectional study design was used. A total of 97 family caregivers of patients with chronic diseases were involved in this study with inclusion and exclusion criteria. The results showed that family caregivers aged an average of 45.71 ± 13.94 years with a minimum age of 20 years and a maximum age of 83 years, 69 people (71.1%) were female, 46 people (47.4%) had high school education level, 58 people (59.8%) was employee, 41 people (42.3%) have a relationship with patients as housewife, and 69 people (71.1%) are willing to build a support group. The conclusion of this study is expected to be the foundation in creating a support group in the family caregivers of patients with chronic diseases.